Невеста и Чудовище: [роман] / Нина Васина - Васина Нина Степановна (Детектив не для всех, 2008)
Экземпляры: ф.9 (20210323☮) / Инвентарный номер: 61258 / Цена: 30.00 / Авт.знак: В 19 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6